RANCANG BANGUN SISTEM TRANSMISI PADA MESIN PENGERING MAGGOT - Ramdani, Rizki; Saleh, Agus; Syafwan, Elvathna (Jurnal TEDC, 2023)
Maggot black solder fly (maggot black solder fly) is the larvae of the black solder fly, many are found in various tropical countries, especially in Indonesia. On average, people in Indonesia dispose of food waste about 300 Kg every year, the amount of food waste is a problem that must be addressed. resolved Utilizing organic waste as a feed medium for black solder fly maggots is one way of processing and utilizing organic waste. The main driver of this machine is an electric motor. Power is transmitted through the pulley and the V- belt to the gearbox and then shaft to generate rotation. Here the electric motor and belt-pulley transmission have an important role. Namely, the electric motor as the main driver and the belt-pulley act as the power transmission system,which is where the selection of a V-bel for transmisi power has the advantage of producing greater power at a relative low voltage. So on this occasion the author designed a V-belt transmission, the pulley-shaft that is right for the black army fly maggot dryer.